Conselho Escolar: avaliação de um espaço democrático em construção no município de Fortaleza - Ferreira, Maria Nilce da Silva (2015)
This study argues about the role of School Councils as a tool to encourage participation within the educational environment of Fortaleza municipality, and evaluates its contribution for the exercise of democratic autonomy in local public education institutions. The historical path’s reconstruction of democracy in Brazil is indispensable for a correct interpretation of a process that inaugurated democratic administration of schools by the Brazilian State. This research aims at determining if the mentioned democratic development is shaped within an actual configuration by means of the Schools Councils’ actuation, besides bringing to light the limits imposed on those collegiate groups that hinder successful participation for a collectively produced work which is still incipient within the educational environment. For this, it is necessary that research goes as far as accessing the educational policies’ core of Brazil’s historical context in order to identify what political, social and economic structural conditions shape the process. Starting with this configuration it will be possible to unveil instruments of democratic administration (autonomy, participation, decentralization) which were implemented for the educational public system in Fortaleza municipality; besides, it will help researchers to understand the democratization process of public education as recommended by local and national legislation. The time span for this research stretches from 2011 to 2013. For this study, bibliographic, documentary and empirical researches were carried out, including development of in place participation and deep-focused interviews. The resulting evaluations point to discrepancies among those who interpret the theorists of democracy as well as among those who resort for guidance to the current legal ordainment related to democratic administration of schools.